(3Pjd dH GddHGH aj GdCfSGH ddSjhWis - (3CMeO GdYLeis; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s ((3eMeO VejQ GdMb GdChQOi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hCaVd GdUdGI Ke GdJSdje Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GfXQ Qbe (B" 676" (3JGQjNs
(3LQO GdPjd JdejP GdYLei (B" (3YHO GdQMef GdCTehfi (B" (3ai SfI (B1089 (3ef gGeT fSNJg ef dH GddHGHs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs